(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article provides an in-depth analysis of the linguistic aspects of medical terminology. The author demonstrates how medical terms have entered literary language, their logical and conceptual foundations, and the interconnections between terms and concepts within various scientific approaches. The study highlights both theoretical and practical aspects of terms from the perspective of modern linguistics. Additionally, the article offers detailed information on types of terms, their roles in social and scientific communication, and their usage in different fields. This work is intended for researchers and students interested in studying terminological systems in linguistics.